RECONSTRUCTION OF ZAKAT GOVERNANCE BASED ON MAQASID AL-SYARI‘AH IN THE DIGITAL AGE - Ahmad Muhtar Syarofi; M. Amin Ilyas; Prayudi Kumala; Istiadah; Ach. Faqih Supandi (STAI Nusantara Kota Banda Aceh, 2026)
Digital transformation has fundamentally altered the landscape of zakat management as one of the main pillars of Islamic economic instruments, playing a strategic role in poverty alleviation and the equitable distribution of welfare amongst the Muslim community. Advances in information technology have opened up opportunities for zakat collection agencies to enhance the effectiveness of zakat fund collection, distribution and reporting through digital platforms, mobile applications, electronic payments and even blockchain technology. However, the digitalisation of zakat also presents serious challenges, including data security vulnerabilities, the risk of technological misuse, low levels of digital literacy amongst the public, and the urgent need to ensure that all digital mechanisms remain aligned with the principles of Islamic Sharia.This study aims to analyse the reconstruction of zakat governance based on maqāṣid al-syarī’ah in the digital age as a normative-operational framework for realising effective, transparent, and community-benefit-oriented zakat management. The research employs a library-based study method with a descriptive-analytical approach, utilising a review of scientific literature, zakat regulations, contemporary fiqh fatwas, and relevant studies in Islamic economics.The research findings indicate that the digitalisation of zakat must be directed towards achieving the al-kulliyyāt al-khams, namely the protection of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), reason (ḥifẓ al-'aql), lineage (ḥifẓ al-nasl), and wealth (ḥifẓ al-māl). Every technological innovation must undergo a Sharia compliance assessment to ensure its permissibility, fairness and benefit. Digital implementation must strengthen institutional transparency, managerial accountability, distribution efficiency, and the sustainable economic empowerment of the mustahik. Therefore, the restructuring of zakat governance necessitates a harmonious integration between technological advancement and adherence to Sharia, so that the maqāṣid al-syarī’ah serve as an operational compass in every policy regarding the integrity of digital zakat management.